THE PLANNING NON-PERSONAL INTERPRETATION MEDIA OF HISTORY IN WANA WISATA KAWAH PUTIH BANDUNG REGENCY - Monika, Lela; Rahmafitria, Fitri; Supriatna, Upi (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
This study aims to design non-personal interpretation media to provide knowledge and education for tourists. The theme applied to non-personal interpretation media planning is the History of Kawah Putih using the Interpretation and Map Board. This research uses qualitative method and quantitative method. The results showed that non-personal media could provide new knowledge or education to visitors about the Kawah Putih. The new knowledge that tourists get from this media is Gunung Patuhas’ characteristics, Kawah Putih and Kawah Saat formation process, Kawah Putihs’ characteristics, and Goa Bekas Tambang Belerang. In addition, this media also helps tourists to know the distribution of facilities in the area Kawah Putih.